Opportunities and challenges of pain-related myocardial ischemia-reperfusion injury - Jiang, Wenhua; Yin, Yue; Gu, Xiaoming; Zhang, Zihui; Ma, Heng (Frontiers in Physiology, 2022)
Pain is one of the most serious problems plaguing human health today. Pain is not an independent pathophysiological condition and is associated with a high impact on elevated disability and organ dysfunction. Several lines of evidence suggested the associations of pain with cardiovascular diseases, especially myocardial ischemia-reperfusion (I/R) injury, while the role of pain in I/R injury and related mechanisms are not yet comprehensively assessed. In this review, we attempted to explore the role of pain in myocardial I/R injury, and we concluded that acute pain protects myocardial ischemia-reperfusion injury and chronic pain aggravates cardiac ischemia-reperfusion injury. In addition, the construction of different pain models and animal models commonly used to study the role of pain in myocardial I/R injury were discussed in detail, and the potential mechanism of pain-related myocardial I/R injury was summarized. Finally, the future research direction was prospected. That is, the remote regulation of pain to cardiac function requires peripheral pain signals to be transmitted from the peripheral to the cardiac autonomic nervous system, which then affects autonomic innervation during cardiac ischemia-reperfusion injury and finally affects the cardiac function.